1997
DOI: 10.1097/00004836-199707000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplastic (Metaplastic) Polyposis of the Colorectum Associated with Adenomas and an Adenocarcinoma

Abstract: Hyperplastic (metaplastic) polyposis associated with adenoma and adenocarcinoma of the colorectum is rare. We describe a 55-year-old man with hyperplastic polyposis associated with multiple adenomas and an adenocarcinoma who underwent total colectomy. We found at least 200 polyps in the surgical specimen. Nearly all of the polyps were hyperplastic, and some were adenomas. Furthermore, some hyperplastic polyps had adenomatous areas. This indicates the transformational sequence of a hyperplastic polyp to adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…5,14,18 In short, despite similar histologic appearances, there seems to be a subset of these polyps that may be far more ominous and carry a significant risk of developing into a colorectal cancer, or at least serve as a marker for the development of colorectal cancer. 8,12,[19][20][21][22] In contradistinction to the ubiquitous scenario of several small distal hyperplastic polyps, patients with hyperplastic polyposis are demonstrably unique. A variety of definitions of hyperplastic polyposis have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,18 In short, despite similar histologic appearances, there seems to be a subset of these polyps that may be far more ominous and carry a significant risk of developing into a colorectal cancer, or at least serve as a marker for the development of colorectal cancer. 8,12,[19][20][21][22] In contradistinction to the ubiquitous scenario of several small distal hyperplastic polyps, patients with hyperplastic polyposis are demonstrably unique. A variety of definitions of hyperplastic polyposis have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Polyp numbers range from 5 to well over 100, with most cases having between 40 and 100 lesions (51). A characteristic feature of HPP is the diverse range of polyp types, ranging from diminutive hyperplastic polyps to larger SSA, SA, and MP as well as traditional adenomas (52)(53)(54). Recently, Burt and Jass (55) developed a working definition of HPP, namely (a) at least five proximal hyperplastic polyps two of which are >10 mm in diameter, or (b) any number of HPs proximal to the sigmoid colon in an individual with a first-degree relative with HPP, or (c) >20 hyperplastic polyps distributed throughout the colon.…”
Section: Hyperplastic Polyposis As a Predisposition To Serrated Neoplmentioning
confidence: 99%
“…15 Not surprisingly, the finding of multiple serrated adenomas in the setting of HPS has led to speculation that individuals with this condition also share a significant increase in cancer risk that is analogous to the increased risk seen in adenomatous polyposis. 4,8 This contention is supported by the fact that 18 of the 49 cases (35%) of hyperplastic polyposis or serrated adenomatous polyposis reported in the literature have been associated with synchronous colorectal carcinomas.…”
mentioning
confidence: 94%
“…11 Although seen only rarely in sporadic lesions, it has been reported to a greater though variable extent in HPS, 8,10 often as foci of adenomatous dysplasia. 4,[12][13][14] It has been suggested that the atypia seen in sporadic serrated adenomas reflects neoplastic progression in an otherwise hyperplastic or metaplastic lesion and that such lesions may represent an alternative pathway to colorectal carcinogenesis. 15 Not surprisingly, the finding of multiple serrated adenomas in the setting of HPS has led to speculation that individuals with this condition also share a significant increase in cancer risk that is analogous to the increased risk seen in adenomatous polyposis.…”
mentioning
confidence: 99%